Análise de parâmetros clínicos e termográficos da pele facial de mulheres em diferentes faixas etárias com e sem efeito da toxina botulínica - Freitas, Camila Tatyanne Santos de (2025)
Aging is a complex biological phenomenon that leads to structural and functional changes in various body systems, especially the skin. Infrared thermography is a non-invasive and promising technique for assessing these changes, enabling a sensitive and effective analysis of cutaneous thermal distribution. The aim of this study was to analyze and compare the temperature distribution on the skin surface of women from different age groups, with and without the application of botulinum toxin, using infrared thermography. The sample consisted of 137 women, determined through sample size calculation, and divided into three age groups (18–24 years; 25–45 years; 46–65 years), selected from the Department of Dentistry at the State University of Paraíba (UEPB), Campus I, in Campina Grande, PB. Among these participants, 46 women had undergone botulinum toxin treatment. The study was structured in three distinct phases, as follows: in the first phase, participants underwent a detailed anamnesis, addressing aspects of general health, facial health, and skincare habits. Additionally, they completed a questionnaire based on the Baumann Skin Type Classification System. In the second phase, participants were referred to the Thermography Laboratory at UEPB, Campus I, for acquisition of thermographic images using a FLIR T650 Infrared portable infrared sensor camera. In the third phase, participants underwent a thorough clinical examination, in which specific topographic points on the face were measured. Simultaneously, skin hydration, oiliness, and elasticity were assessed through electrical impedance analysis (Skin Up). For statistical analysis, ANOVA and the Kruskal-Wallis test were applied to assess skin temperatures. The results revealed that younger women exhibited higher facial temperatures and that temperature varied according to the menstrual cycle. The application of botulinum toxin did not significantly alter facial thermal patterns, although a tendency toward lower temperatures in treated areas was observed through the independent t-test and the Mann-Whitney test. Moderate negative correlations between age and temperature in specific facial regions—particularly among women who had not received botulinum toxin—were identified using Pearson and Spearman tests. It is concluded that facial cutaneous temperature distribution presents significant variations across different age groups, with higher values observed in younger women. However, the application of botulinum toxin did not result in expressive thermographic changes, indicating that its use does not significantly interfere with facial thermal patterns.